2020
DOI: 10.1161/jaha.119.014142
|View full text |Cite
|
Sign up to set email alerts
|

Stim1 Polymorphism Disrupts Immune Signaling and Creates Renal Injury in Hypertension

Abstract: Background Spontaneously hypertensive rats of the stroke‐prone line ( SHR ‐A3) develop hypertensive renal disease as a result of naturally occurring genetic variation. Our prior work identified a single‐nucleotide polymorphism unique to SHR ‐A3 that results in truncation of the carboxy terminus of STIM 1. The SHR ‐B2 line, which is also hypertensive but resists hypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…These results indicated that HN is possibly a disorder caused by abnormalities in transcription activity and imbalance in redox homeostasis. As previously reported, the abnormal transcription activity of genes (Zhang et al, 2015;Dhande et al, 2020) and oxidative stress (Majzunova et al, 2019;Nguyen et al, 2020) can be a cause or, more often, a potentiating factor for hypertension and hypertensive renal disease. Besides this, three hub genes associated with HN, namely, POLR2L, POLR2G, and POLR2I, were identified by PPI network analysis.…”
Section: Discussionmentioning
confidence: 65%
“…These results indicated that HN is possibly a disorder caused by abnormalities in transcription activity and imbalance in redox homeostasis. As previously reported, the abnormal transcription activity of genes (Zhang et al, 2015;Dhande et al, 2020) and oxidative stress (Majzunova et al, 2019;Nguyen et al, 2020) can be a cause or, more often, a potentiating factor for hypertension and hypertensive renal disease. Besides this, three hub genes associated with HN, namely, POLR2L, POLR2G, and POLR2I, were identified by PPI network analysis.…”
Section: Discussionmentioning
confidence: 65%
“… 114 Replacement of the defective Stim1 allele in SHR-A3 remedies defective Ca ++ signaling and substantially reduces renal injury without effect on preinjury BP. 114 Rare genetic defects in humans producing complete loss of Stim1 function are associated with autoimmune disease attributable to disturbed antibody formation. 115 , 116 Thus, SHR-A3 has accumulated 2 gene variants with important consequences for antibody formation that drive renal injury in the presence of hypertension.…”
Section: Animal Model Approaches To Genetics Of Progressive Renal Diseasementioning
confidence: 99%
“…They concluded that there are one or more genes in the IgH region of chromosome 6 likely influence renal injury by altering B‐ and T‐cell function and the immune response. In subsequent studies, they identified a truncation in another gene ( Stim1 ) in the SpSHR rats that contribute to the susceptibility to renal injury (Dhande et al., 2020). STIM1 is an endoplasmic reticulum (ER) calcium sensor that plays a central role in lymphocyte effector and regulatory function.…”
Section: Genes Involved In the Alteration Of Immune Cell Functionmentioning
confidence: 99%
“…STIM1 is an endoplasmic reticulum (ER) calcium sensor that plays a central role in lymphocyte effector and regulatory function. Congenic replacement of truncated Stim1 with the wild‐type allele restored a major defect in immune function in SHR‐A3, a line of SpSHR, and the ability of hypertension to elicit damage to the kidney was reduced in this model (Dhande et al., 2020). These results suggest that the major immune phenotype produced by the Stim1 mutation participates in renal injury in SHR‐A3, and this may include injury contributed by autoantibody formation that interferes with T‐cell signaling to program antibodies producing by B cells.…”
Section: Genes Involved In the Alteration Of Immune Cell Functionmentioning
confidence: 99%